1975
DOI: 10.1002/ar.1091830207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strontium, cobalt and fluoride on rat incisor enamel formation

Abstract: This investigation examined ultrastructurally the entire period of development of alterations in formative ameloblasts and the enamel which they produce following injection with fluoride, strontium, and cobalt ions. Rats injected with these ions were sacrificed at intervals of 1, 2, 4, 8, 16, 24 and 48 hours to elucidate the sequence and detail of cytologic and cell product alterations which occur. Undecalcified sections of rat incisor teeth were studied using electron microscopy and microradiography. All thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…On the basis of these data, some of the older reports of the effects of parenterally applied fluoride on enamel formation in rats show levels that appear to be within the toxic range, and need to be interpreted with caution (Neiman and Eisenmann, 1975;Chen and Eisenmann, 1984;Ashrafi et al, 1988). Indeed, some studies have reported toxic effects after fluoride injection, including a delay in growth (less gain in body weight), immobility, and change of skin color (Mörnstad and Hammarström, 1978), or even death a few hours after injection of fluoride (Larsen et al, 1981).…”
Section: The Rat As a Model For Enamel Fluorosismentioning
confidence: 88%
See 1 more Smart Citation
“…On the basis of these data, some of the older reports of the effects of parenterally applied fluoride on enamel formation in rats show levels that appear to be within the toxic range, and need to be interpreted with caution (Neiman and Eisenmann, 1975;Chen and Eisenmann, 1984;Ashrafi et al, 1988). Indeed, some studies have reported toxic effects after fluoride injection, including a delay in growth (less gain in body weight), immobility, and change of skin color (Mörnstad and Hammarström, 1978), or even death a few hours after injection of fluoride (Larsen et al, 1981).…”
Section: The Rat As a Model For Enamel Fluorosismentioning
confidence: 88%
“…In severe cases, prismless enamel is found within prismatic inner enamel. At these locations, formation of prismatic enamel had been abruptly interrupted during fluoride insult, during which prismless enamel had formed; after recovery, the prismatic enamel continued to form (e.g., Neiman and Eisenmann, 1975;Chen and Eisenmann, 1984;Suckling et al, 1988;Monsour et al, 1989;Kierdorf and Kierdorf, 1997;Kierdorf et al, 2000Kierdorf et al, , 2004.…”
Section: Possible Mechanisms Of Fluoride Action On Enamel Formation Dmentioning
confidence: 99%
“…Animal studies have shown that Sr causes at least disturbances in ameloblast morphology and amelogenesis [Weinmann, 1943;Neiman and Eisenmann, 1975], whereas several reports exist on Sr-mediated dentin hypomineralisation [e.g. Yaeger and Eisenmann, 1963].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to its effects on dentin, Sr has been shown to cause disturbances in ameloblast morphology and amelogenesis [Weinmann, 1943;Neiman and Eisenmann, 1975] in rats when 6 injected. White et al [1980] demonstrated that the enamel organ limits Sr uptake in both the secretory and maturation phases of enamel formation.…”
Section: Sr Studies In Animals Sr Effects On Dentin and Enamelmentioning
confidence: 99%
“…Additional evidence that a substantial pool of calcium is available during the fluoride response is sup ported by the fact that pre-existing enamel continues to mineralize, forming a hypermineralized layer while newly secreted matrix fails to mineralize. This has been con firmed by microradiographic studies [9] as well as organ culture of mineralizing tooth germs exposed to various levels of fluoride [18]. There is growing evidence to sup port the view that fluoride may cause alterations in the composition of newly secreted enamel matrix.…”
Section: Effects O F Fluoride Ionmentioning
confidence: 95%